Predictors of SARS-CoV-2 RNA From Nasopharyngeal Swabs and Concordance With Other Compartments in Nonhospitalized Adults With Mild to Moderate COVID-19. (11th November 2022) - Moser, Carlee; Li, Jonathan Z; Eron, Joseph J; Aga, Evgenia; Daar, Eric S; Wohl, David A; Coombs, Robert W; Javan, Arzhang Cyrus; Bender Ignacio, Rachel A; Jagannathan, Prasanna; Ritz, Justin; Sieg, Scott F; et al.
Abstract: Background: Identifying characteristics associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA shedding may be useful to understand viral compartmentalization, disease pathogenesis, and risks for viral transmission. Methods: Participants were enrolled August 2020 to February 2021 in ACTIV-2/A5401, a placebo-controlled platform trial evaluating investigational therapies for mild-to-moderate coronavirus disease 2019 (COVID-19), and underwent quantitative SARS-CoV-2 RNA testing on nasopharyngeal and anterior nasal swabs, oral wash/saliva, and plasma at entry (day 0, pretreatment) and days 3, 7, 14, and 28. Concordance of RNA levels (copies/mL) across compartments and predictors of nasopharyngeal RNA levels were assessed at entry (n = 537). Predictors of changes over time were evaluated among placebo recipients (n = 265) with censored linear regression models. Results: Nasopharyngeal and anterior nasal RNA levels at study entry were highly correlated ( r = 0.84); higher levels of both were associated with greater detection of RNA in plasma and oral wash/saliva. Older age, White non-Hispanic race/ethnicity, lower body mass index (BMI), SARS-CoV-2 immunoglobulin G seronegativity, and shorter prior symptom duration were associated with higher nasopharyngeal RNA at entry. In adjusted models, body mass index and race/ethnicity associations were attenuated, but the association with age remained (for every 10 years older, mean nasopharyngeal RNA was 0.27 log10 copies/mL higher; P < .001). Examining longitudinal viral RNA levels among placebo recipients, women had faster declines in nasopharyngeal RNA than men (mean change, −2.0 vs −1.3 log10 copies/mL, entry to day 3; P < .001). Conclusions: SARS-CoV-2 RNA shedding was concordant across compartments. Age was strongly associated with viral shedding, and men had slower viral clearance than women, which could explain sex differences in acute COVID-19 outcomes.